Exploring the Concept of Maqasid al-Sunnah to Understand the Higher Objectives of the Sunnah - Mesbahul Hoque; Zulhilmi Bin Mohamed Nor; Muneer Ali Abdul Rab; Kauthar Abd Kadir; Yuslina Mohamed (HUMAN RESOURCE MANAGEMENT ACADEMIC RESEARCH SOCIET, 2024)
International Journal of Academic Research in Business & Social SciencesVol 13, Issue 11 Page (767-775)